Statistical Shape Model-Based Tibiofibular Assessment of Syndesmotic Ankle Lesions using Weightbearing CT. Issue 4 (November 2022) - Peiffer, Matthias; Last, Matthias; Burssens, Arne; Mits, Sophie De; Buedts, Kristian; Victor, Jan M.; Audenaert, Emmanuel
Category: Trauma; Ankle Introduction/Purpose: Forced external rotation is hypothesized as the key mechanism of syndesmotic ankle injuries, inducing a three-dimensional deviation from the normal distal tibiofibular joint alignment. These lesions, especially when subtle, present a deceitful diagnostic challenge. Current diagnostic imaging modalities are impeded by a two-dimensional assessment, without considering ligamentous stabilizers. Accurate diagnosis of syndesmotic lesions should involve 3D weightbearing osseous imaging in combination with - preferably automated- inclusion of patient-specific ligamentous information. Therefore, our aim is two-fold: (1) to construct a three-dimensional articulated statistical shape model of the normal distal tibiofibular joint with inclusion of ligamentous morphometry and (2) to detect differences in predicted syndesmotic ligament length of patients with syndesmotic lesions with respect to normative data. Methods: Training data comprised non-weightbearing CT scans from asymptomatic controls (N= 76, Mean age 63 +/- 19 years), weightbearing CT scans from patients with syndesmotic ankle injury (N = 13, Mean Age 35 +/- 15 years) and their weightbearing healthy contralateral side (N = 13). CT scan segmentation was used to generate 3D bone models in the control and patient group. All ankles were aligned based on the tibia. Path and length of the syndesmotic ligaments were predicted using a discrete element model, wrapped around bony contours. Statistical shape model evaluation was based on accuracy, generalization and compactness. The predicted ligament length in patients with syndesmotic lesions was compared to healthy controls by use of two-tailed Two- Sample student's t-test. Results: Our presented skeletal shape model described the training data with an accuracy of 0.23 +/- 0.028 mm. Mean prediction accuracy of ligament insertions was 0.53 +/- 0.12 mm. Mean length of the Anterior inferior tibiofibular ligament was 12.26 +- 1.89mm for the control cases, 12.32 +- 1.58 mm for the contralateral cases and 14.13 +- 1.48 mm for the cases with syndesmotic lesions. Statistically significant differences were found between the latter two (95% CI [ 0.323.29], p = 0.017) There was a significant correlation between presence of syndesmotic injury and the positional alignment between the distal tibia and fibula (r = 0.873, p < 0, 001). Conclusion: Statistical shape modelling combined with patient-specific ligament wrapping techniques can facilitate the diagnostic workup of syndesmotic ankle lesions under weightbearing conditions. In doing so, an increased anterior tibiofibular distance was detected, corresponding to an 'anterior open-book injury' of the ankle syndesmosis as a result of anterior inferior tibiofibular ligament elongation/rupture (Figure 1).